2017
DOI: 10.1161/circulationaha.116.026910
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Midwall Late Gadolinium Enhancement and Sudden Cardiac Death in Patients With Dilated Cardiomyopathy and Mild and Moderate Left Ventricular Systolic Dysfunction

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
224
1
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 300 publications
(239 citation statements)
references
References 36 publications
9
224
1
5
Order By: Relevance
“…Mid-wall LGE occurs in around 1/3 of patients with NIDCM and represents areas of replacement fibrosis, which are thought to act as substrate for re-entrant ventricular tachycardia (7). In keeping with this, mid-wall LGE predicts a 5-9 fold increased risk of SCD and malignant ventricular arrhythmias in patients with NIDCM over the following 5 years (7,8).…”
Section: Fraction (Lvef) (Hf-ref) Has Been Questioned Following the Dmentioning
confidence: 89%
“…Mid-wall LGE occurs in around 1/3 of patients with NIDCM and represents areas of replacement fibrosis, which are thought to act as substrate for re-entrant ventricular tachycardia (7). In keeping with this, mid-wall LGE predicts a 5-9 fold increased risk of SCD and malignant ventricular arrhythmias in patients with NIDCM over the following 5 years (7,8).…”
Section: Fraction (Lvef) (Hf-ref) Has Been Questioned Following the Dmentioning
confidence: 89%
“…A further study21 demonstrated a significant association between MWF and all-cause mortality (p<0.001) even after adjustment for EF; 29.6% of those with fibrosis reached the arrhythmic end points of SCD or aborted SCD versus 7% of those without fibrosis (p<0.001). Recently, the question of whether LGE signifies risk in those with DCM and EF>40% was studied 26. A total of 399 patients were enrolled, 25% had MWF, mean EF was 49% and median follow-up was 4.6 years.…”
Section: The Emerging Risk Stratification Method: Late Gadolinium Enhmentioning
confidence: 99%
“…[25][26][27][28] Quantification of LGE can represent a wide variety of tissue processes and has emerged as a diagnostic tool in ischemic heart disease to measure areas of infarction 29 and for risk stratification in ischemic 30,31 and nonischemic heart disease. [32][33][34] Although in clinical practice decreasing cardiac enzymes and inflammatory markers are commonly interpreted as being indicative of resolving myocarditis, no cardiac imaging studies have confirmed this assumption as of today. In this study, we sought to evaluate whether absolute serum levels of routine laboratory parameters at the time of diagnosis predict persistence of LGE on CMR at 3 months and whether their decline from baseline to 3-month follow-up correlates with improvement of LGE.…”
mentioning
confidence: 99%